Snapshots of teacher identity in English as an additional language or dialect (EAL/D) education in Australia: Insights for pre-service educators - Joshua Matthews (Australian Journal of Applied Linguistics)
This article presents a series of practitioner-focused identity “snapshots” drawn from interviews with experienced teachers of English as an Additional Language or Dialect (EAL/D) working in Australian schools. It supports pre-service and early-career EAL/D educators in understanding the lived realities of Australian EAL/D teaching through thematically organised insights based on teachers’ personal narratives and reflections. Based on interviews exploring personal experiences, classroom practices, and sociopolitical contexts, five key identity themes were identified: (1) personal background shapes teaching identity, (2) teaching is deeply student-centred, (3) institutional and policy challenges impact classroom practice, (4) emotional labour is a significant part of the job, and (5) EAL/D teachers often become advocates. These snapshots offer accessible, authentic accounts of Australian EAL/D teaching, designed to support reflective practice and professional learning in teacher education programs. Accompanied by a practical identity reflection toolkit, they translate teacher narratives into structured, applied learning. Addressing a gap in Australian EAL/D research, the study centres teacher voice through thematically organised practitioner accounts purpose-built to scaffold identity work in teacher preparation.